The Effect of Magnesium Citrate on %FEV1, %PEFR, and Asthma Control Test Score in Patients with Controlled Asthma and Uncontrolled Asthma - Atmojo, Anang Purwoko; Sutanto, Yusup Subagio; Adhiputri, Artrien; Reviono, Reviono; Setijadi, Ana Rima (Jurnal Respirologi Indonesia, 2025)
Background: Asthma is one of the most common non-communicable diseases in the world and affected an estimated 262 million people in 2019. Magnesium is one of the nutrients known to improve lung function in asthma by inhibiting the production of proinflammatory cytokines, exhibiting anti-inflammatory benefits, and having beneficial muscle-relaxing and bronchodilatation effects. Measurement of percent predicted forced expiratory volume in 1 second (%FEV1), percent predicted peak expiratory flow rate (%PEFR), and asthma control test (ACT) score is are indicator of lung function. Magnesium citrate may be used as an adjunct therapy in patients with controlled and uncontrolled asthma. Methods: Clinical trial research with quasi quasi-experimental method using a pre-test and post-test design. The study subjects were 34 controlled and uncontrolled asthma patients at the outpatient clinic of Universitas Sebelas Maret Hospital and dr. Soehadi Prijonegoro Hospital in February - March 2023, using consecutive sampling. The control group (n=17) received standard therapy, while the treatment group (n=17) received standard therapy plus 300 mg magnesium citrate for 42 days. Serum magnesium level, %FEV1, %PEFR, and ACT score were measured at enrollment and on the forty-third day of treatment. Results: There were significant differences between the treatment group compared to the control group in increasing %PEFR (P=0.001), increasing ACT score (P=0.011), and increasing %FEV1 (P=0.071). Conclusion: Administration of magnesium citrate to patients with controlled and uncontrolled asthma can increase levels of %PEFR, ACT score, and %FEV1.